2021
DOI: 10.3390/life11090919
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interleukin-17 Inhibitor Therapy on Arterial Intima-media Thickness among Severe Psoriatic Patients

Abstract: Background: Psoriasis is frequently accompanied by cardiovascular diseases based on the shared immunopathogenic pathway. Authors determined the effect of interleukin (IL)-17 inhibitor therapy on arterial intima-media thickness (IMT) among severe psoriatic patients. Methods: Thirty-one severe psoriatic patients were enrolled. Twenty received secukinumab and 11 received ixekizumab. Before treatment initiation and after 6 months, the carotid-brachial-femoral IMT, the Psoriasis Area Severity Index (PASI), the Derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 36 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, in a randomized study in patients with psoriasis, impaired endothelial function at baseline, as measured by flow-mediated dilation, was modestly restored after 52 weeks of secukinumab treatment [ 44 ]. In another study, anti-IL-17 therapy showed ameliorations in arterial intima-media thickness after 6 months of treatment in patients with severe psoriasis, suggesting a potential beneficial effect of anti-IL-17 therapy on cardiovascular complications of systemic inflammation [ 45 ]. Secukinumab decreased hsCRP levels over 52 weeks in patients with psoriasis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a randomized study in patients with psoriasis, impaired endothelial function at baseline, as measured by flow-mediated dilation, was modestly restored after 52 weeks of secukinumab treatment [ 44 ]. In another study, anti-IL-17 therapy showed ameliorations in arterial intima-media thickness after 6 months of treatment in patients with severe psoriasis, suggesting a potential beneficial effect of anti-IL-17 therapy on cardiovascular complications of systemic inflammation [ 45 ]. Secukinumab decreased hsCRP levels over 52 weeks in patients with psoriasis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“… Marovt et al [ 38 ] 2020 Ultrasonography and PWA PsO 15 None (change from baseline) Biologics [(anti-IL-12/23 and IL-17) secukinumab, ustekinumab and ixekizumab] PWV, augmentation index and IMT Biologics targeting the IL-23/IL-17 axis had no effect on vascular structure (IMT) and PWV after 6 months of treatment. Piros et al [ 39 ] 2021 Ultrasound PsO 31 None (change from baseline) Anti-IL-17 [secukinumab, ( N = 20), ixekizumab ( N = 11)] The carotid, brachial and femoral IMT Anti-IL-17 treatment was associated with reduced carotid, brachial and femoral atherosclerosis (IMT) after 6 months of treatment. Gelfand et al [ 40 ] 2022 FDG-PET/CT PsO 70 None (change from baseline) Apremilast Vascular inflammation (TBR) in entire aorta Apremilast had no effect on aortic vascular inflammation after 16 and 52 weeks of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…RCTs with longer follow-up periods or further well-designed longitudinal studies using data from national and international registers are necessary. For the novel IL-23/Th-17 axis inhibitors, although some studies have shown beneficial effects on the surrogate markers of CV diseases, 107,108 recently published observational studies suggest that IL-12/23, IL-17 and IL-23 inhibitors might be associated with the risk of certain severe CV events. [109][110][111][112] Further comparative studies using real-world data on the effect of different biological therapies of IMIDs on CV risk are needed.…”
Section: Implications For Researchmentioning
confidence: 99%